Microglia are less pro‐inflammatory than myeloid infiltrates in the hippocampus of mice exposed to status epilepticus. Issue 8 (1st June 2016) - Vinet, Jonathan; Vainchtein, Ilia D.; Spano, Carlotta; Giordano, Carmela; Bordini, Domenico; Curia, Giulia; Dominici, Massimo; Boddeke, Hendrikus W. G. M.; Eggen, Bart J. L.; Biagini, Giuseppe
Abstract : Activated microglia, astrogliosis, expression of pro‐inflammatory cytokines, blood brain barrier (BBB) leakage and peripheral immune cell infiltration are features of mesial temporal lobe epilepsy. Numerous studies correlated the expression of pro‐inflammatory cytokines with the activated morphology of microglia, attributing them a pro‐epileptogenic role. However, microglia and myeloid cells such as macrophages have always been difficult to distinguish due to an overlap in expressed cell surface molecules. Thus, the detrimental role in epilepsy that is attributed to microglia might be shared with myeloid infiltrates. Here, we used a FACS‐based approach to discriminate between microglia and myeloid infiltrates isolated from the hippocampus 24 h and 96 h after status epilepticus (SE) in pilocarpine‐treated CD1 mice. We observed that microglia do not express MHCII whereas myeloid infiltrates express high levels of MHCII and CD40 96 h after SE. This antigen‐presenting cell phenotype correlated with the presence of CD4 pos T cells. Moreover, microglia only expressed TNFα 24 h after SE while myeloid infiltrates expressed high levels of IL‐1β and TNFα. Immunofluorescence showed that astrocytes but not microglia expressed IL‐1β. Myeloid infiltrates also expressed matrix metalloproteinase (MMP)−9 and 12 while microglia only expressed MMP‐12, suggesting the involvement of both cell types in the BBB leakage that follows SE. Finally, both cell types expressed the phagocytosis receptor Axl, pointing to phagocytosis of apoptotic cells as one of the main functions of microglia. Our data suggests that, during early epileptogenesis, microglia from the hippocampus remain rather immune supressed whereas myeloid infiltrates display a strong inflammatory profile. GLIA 2016 GLIA 2016;64:1350–1362 Main points: After status epilepticus, myeloid infiltrates express high levels of MHCII, IL‐1β and matrix metalloproteinases. Compared to individual infiltrating cells, microglia are relatively immune‐suppressed.